2010
DOI: 10.3177/jnsv.56.331
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Galloyl Moiety in Tea Catechins on Binding Affinity for Human Serum Albumin

Abstract: SummaryThe major catechins of green tea extract are ( Ϫ )-epicatechin (EC), ( Ϫ )-epigallocatechin (EGC), ( Ϫ )-epicatechin gallate (ECg), and ( Ϫ )-epigallocatechin gallate (EGCg). Recent research has indicated that catechins form complexes with human serum albumin (HSA) in blood, and differences in their binding affinity toward HSA are believed to modulate their bioavailability. In this study, we kinetically investigated the interaction between the catechins and HSA immobilized on a quartz-crystal microbalan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In contrast, the UF-filtrate (rich in low molecular weight tannins) and single hydrolysable tannins seem to have either no or only a reversible effect in this assay. In line with this observation, the protein binding efficiency of tannins increases with molecular size [26] and the number of galloyl residues [85], [86], suggesting a tighter binding of high molecular weight tannins to target proteins. In addition to interfering with surface proteins, a virucidal activity (e.g.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, the UF-filtrate (rich in low molecular weight tannins) and single hydrolysable tannins seem to have either no or only a reversible effect in this assay. In line with this observation, the protein binding efficiency of tannins increases with molecular size [26] and the number of galloyl residues [85], [86], suggesting a tighter binding of high molecular weight tannins to target proteins. In addition to interfering with surface proteins, a virucidal activity (e.g.…”
Section: Discussionsupporting
confidence: 67%
“…Polyphenols are also thought to be likely to interact with proteins due to the structural factors of phenolic hydroxyl groups such as their hydrophobicity and hydrogen bonding properties. It has been reported that the binding of proteins and polyphenols produce a water-insoluble complex [ 11 , 12 , 13 , 14 ], and that polyphenols inhibit the toxin activity of staphylococcal proteins [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Although there is a report on the binding interaction analysis of staphylococcal enterotoxin B protein and polyphenols [ 22 ], there is no report on the binding interaction analysis of SEA proteins and polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using fluorescence quenching of the single tryptophan found dissociation constants ( K d ) to HSA of 17 μM [9] and 12.5 μM [10], though such studies can only monitor binding close to Sudlow site I and any other binding will be invisible. A study using quartz crystal microbalance found a K d of 4 μM [11]. Two molecular docking studies of EGCG/BSA binding suggested binding near Sudlow site I [8,12], while another fluorescence study backed by modelling [9] suggested that EGCG binds HSA at a single site, probably at Sudlow site I.…”
Section: Introductionmentioning
confidence: 99%